High performance detection using three different weight blind algorithms in ZF receiver for uplink multi-user massive MIMO in 5G wireless communications - Duangsuwan, Sarun; Teekapakvisit, Chakree (My University, 2018)
A novel of an uplink multi-user massive Multi-Input Multi-Output (MIMO) in 5G wireless communication that is an increasing efficiency of massive MIMO detection, in order to support a very high speed Giga-Wireless (GiWi). One of the most focused on the Zero-Forcing (ZF) receiver, but due to it has no optimal. In this paper, we present blind algorithms to optimize the performance of ZF because of their low complexity. The three different weight blind algorithms are various proposed by using the Conventional Constant Modulus (CCM), Supervised Constant Modulus (SCM), and the Variable Step Size Constant Modulus (VSSCM). The performance results show as a channel response, Mean Square Error (MSE), and Bit Error Rate (BER) is discussed. It can be shown that the proposed blind algorithms can optimal efficiency of ZF receiver under an assumption of no required CSI.
Keywords: 5G wireless communication; Multi-user massive MIMO system; Three different blind algorithms; ZF receiver